Adaptative Variation in a Neotropical Dung Beetle: Females and Gamma Males Present Tunneler Morphology, While Beta and Alpha Males Present Wing Morphology for Velocity - Pedro Henrique deOliveira Ribeiro; Nicholas Ferreira Camargo; Marina Regina Frizzas (Ecology and Evolution)
ABSTRACT In evolutionary terms, plastic traits can covary, providing adaptive value by compensating for certain characteristic costs or enhancing fitness. This combination of traits is expected in species with significant intrapopulation ecological variation, like insects. In the Phanaeini tribe, males and females have distinct nesting behaviors, and the alpha, beta, and gamma morphotypes of trimorphic males display different reproductive strategies. Although phenotypic integration of wings and protibiae associated with horn size occurs in dung beetles, this study focuses on the morphological and functional variation of these and other structures due to behavioral differences and reproductive strategies between sexes and male morphotypes. We used a geometric and functional morphometric approach to investigate the variation in plasticity of structures (clypeus, protibia, elytra, and membranous wing), their integration with horn size in males, and flight biomechanics in the trimorphic dung beetle Oxysternon palemo (Scarabaeinae: Phanaeini). Comparing different sexes and morphotypes, we tested for significant differences associated with various reproductive and behavioral strategies. Adaptive morphological differences were found in all structures in at least three of the four groups (females and alpha, beta, and gamma males), along with clear sexual dimorphism in the protibia. In alpha males, fossorial structures enhance resource partitioning and confrontations, whereas in females and gamma males, these structures optimize digging and tunnel mobility. We also found integration between the size of pronotal horns and clypeus shape, and between head horn size and wing shape. The variation in elytra morphology, covariation between membranous wings and horns, and flight biomechanics results suggests different reproductive investment and foraging strategies among groups. Alpha and beta males invest in intense flights and rapid resource colonization, whereas gamma males exhibit slower, low‐energy flights with greater reproductive investment. We discuss how trade‐offs between dispersal and reproduction in polyphenic insects shape adaptive variation through plasticity in dung beetle morphotypes.